Intensive, functional training leads to optimal outcomes in a young woman post brain stem hemorrhage due to cerebral cavernous malformation. (2nd June 2020) - Thompson, Kasey; Mattern-Baxter, Katrin
ABSTRACT: Purpose: Cerebral cavernous malformations (CCMs) can cause intracranial hemorrhages and account for 5–15% of all cerebral vascular malformations. The purpose of this retrospective case report is to describe the unusual motor recovery of a young woman following a large hemorrhage of a previously unknown brainstem CCM, otherwise not reported in the literature. Case Description : The patient was a 29-year-old female who presented with severe hemiparesis on the left 6 weeks after a first-ever hemorrhage. She had demonstrated minimal improvement in her motor recovery to date, was dependent on a walker for ambulation, and had no distal left upper extremity function. An intensive evidence-based plan of care over 6 weeks included progressive task-specific strengthening, treadmill training, and dynamic balance training. Outcomes : The patient achieved complete motor recovery, indicated by improvement from 23/66 to 64/66 in the Fugl-Meyer Upper Extremity Subscale score and from 12/30 to 30/30 in the Functional Gait Assessment. She returned to independent ambulation with functional gait speeds and kinematics. Discussion : This case report demonstrates an unusual clinical course of unexpected full recovery in a young woman after a large brainstem CCM after an intensive 6-week course of physical therapy. Other patients with a similar presentation after CCM may benefit from an intensive plan of care. Clinicians should be aware of the possibility of unusual recovery in this population as not to limit expectations for recovery.